Preliminary Study of Profenofos and Difenoconazole Pesticide Residue in Soil and Citrus Fruits from Citrus Farming in Serai Village Kintamani Bangli - I Wayan Muderawan; Luh Mitha Priyanka; I Nengah Suparta (Indonesian Journal of Chemistry and Environment, 2022)
The intensively use of both profenofos and difenoconazole pesticides in Citrus farming in Serai Village Kintamani Bangli may remain as residue in the soil and citrus fruits. This study was performed in order to determine the level of pesticide residues in the soil and the citrus fruits from Citrus farming in Bangli. The pesticide residue levels in the soil and citrus fruit were performed by using solid-liquid extraction (SLE) and detected by high performance liquid chromatography (HPLC). The result shows that the pesticide residue levels in soil, citrus peel and citrus flesh are 0.057±0.002, 0.112±0.013 and 0 mg/L for profenofos and 0.069±0.002, 0.180±0.013 and 0 mg/L for difenoconazole. The results indicated that the soil and citrus peel from citrus farming area in Serai Village Bangli Regency contained both pesticide residues but not the citrus flesh.